Where the conflict really lies : science, religion, and naturalism - Plantinga, Alvin (New York : Oxford University Press, 2011)
This book is a long-awaited major statement by a pre-eminent analytic philosopher, Alvin Plantinga, on one of our biggest debates -- the compatibility of science and religion. The last twenty years has seen a cottage industry of books on this divide, but with little consensus emerging. Plantinga, as a top philosopher but also a proponent of the rationality of religious belief, has a unique contribution to make. His theme in this short book is that the conflict between science and theistic religion is actually superficial, and that at a deeper level they are in concord. Plantinga examines where this conflict is supposed to exist -- evolution, evolutionary psychology, analysis of scripture, scientific study of religion -- as well as claims by Dan Dennett, Richard Dawkins, and Philip Kitcher that evolution and theistic belief cannot co-exist. Plantinga makes a case that their arguments are not only inconclusive but that the supposed conflicts themselves are superficial, due to the methodological naturalism used by science. On the other hand, science can actually offer support to theistic doctrines, and Plantinga uses the notion of biological and cosmological "fine-tuning" in support of this idea. Plantinga argues that we might think about arguments in science and religion in a new way -- as different forms of discourse that try to persuade people to look at questions from a perspective such that they can see that something is true. In this way, there is a deep and massive consonance between theism and the scientific enterprise.
Evolution and Christian belief (1) -- Evolution and Christian belief (2) -- Divine action in the world : the old picture -- The new picture -- Evolutionary psychology and scripture scholarship -- Defeaters? -- Fine-tuning -- Design discourse -- Deep concord : Christian theism and the deep roots of science -- The evolutionary argument against naturalism.
Includes bibliographical references and index.
Keywords: Religion and science; Evolution (Biology) -- Religious aspects -- Christianity; Naturalism -- Religious aspects -- Christianity; Christentum; Evolution; Naturwissenschaften; Religion; Christentum; Evolution; Naturwissenschaften; Religion